Excelling on Campus, Lagging in the Workplace: The Paradox of Gender Equality in Indonesia - Hendika Dwinanda Wicaksana; Surfian Rahmat AP; Syfa Amelia; Muhammad Haikal; Ahmad Prasetya Hady (JPW (Jurnal Politik Walisongo), 2025)
Despite significant advancements in women's higher education in Indonesia, where female enrolment now surpasses that of men, major gender disparities persist in the labor market. This paper investigates the enduring paradox of "Excelling on Campus, Lagging in the Workplace," wherein higher educational attainment for women does not translate into equitable outcomes in labor force participation, remuneration, and career advancement. Employing a qualitative methodology through a systematic literature review, this study synthesizes and critically analyzes existing national data, institutional reports, and academic literature. The analysis is framed by the Feminist Critique of Human Capital Theory, arguing that conventional economic models fail because they ignore the entire sphere of social reproduction the unpaid domestic and caregiving labor that is disproportionately shouldered by women. The findings demonstrate that the participation gap, wage disparities, and the "glass ceiling" are not separate issues but are interconnected manifestations of a system that structurally penalizes women for their socially-mandated reproductive roles. The study concludes that achieving substantive gender equality in Indonesia requires a policy shift beyond merely promoting education, necessitating a fundamental re-evaluation of the value of reproductive labor and the implementation of policies that directly address these structural barriers.